The Role and Place of Terminological Word Combinations in the Terminological Systems of the German, Russian and Tatar Languages - Nailevna Zaripova, Alfiya; Yakovlevna Zaglyadkina, Tatyana; Valerievna Akimova, Olga; Marsovna Sadykova, Dilyara (International Journal of Engineering and Technology, 2018)
The relevance of this article is due to the growing role of word combinations in enriching terminological vocabulary in the German, Russian and Tatar languages. In the center of terminological nomination there are terminological word combinations, which can be interpreted by a more complex structure of terms of a certain professional sphere and concepts in the intellectual activity of professionals. Terminological word combinations allow clarifying the available concept. Terminological word combinations appear at later periods of development of terminological systems. Terms – word combinations are considered to be the most productive way of nominating concepts that undergo changes over time and can be simultaneously used as abbreviations. Terminological word combinations are different from free word combinations and phraseological units. The purpose of the article is to describe the features of a terminological word combination. In addition, the article describes productive models of the formation of terminological word combinations in the German, Russian and Tatar languages. All possible structural types can be combined into substantive-substantive and attributive-substantive word combinations. The materials of the article can be useful in teaching the German, Russian and Tatar languages, as well as for courses in comparative typology and lexicology. The results can also be used in the study of particular terminological systems and in the description of the professional language personality.